Domestic cat - the unspoken threat to wildlife in the sub-urban location of Maribor - Bedrač, Larisa (Acta biologica slovenica, 2024)
The monitoring of domestic cats' prey brought home was conducted between the 13th of March and the 1st of May 2023 in two residential areas near Maribor, Slovenia. This study aimed to provide information about the amount, diversity, and frequency of prey that the cats captured to identify the predatory impact of domestic cats in peri-urban areas. We present the results of the prey return, whether the prey was brought alive or not, and whether it was eaten or not. We further provide information about the predation frequency of domestic cats concerning circadian activity according to weather conditions and air temperature. The frequencies of various taxonomic groups of prey captured were described in relation to land use in a location and species' biology. Our results include a total of 50 records of 12 species (3 species of birds and 9 of mammals). Domestic cats were more active during the mornings and on days without rain, and the frequency of bringing home prey increased with higher temperatures.
Keywords: notranje-zunanja mačka; plen; plenilska aktivnost mačk; primestna območja; prostoživeče živali; temperatura zraka